Perjuangan Umat Islam Dalam Merebut Kemerdekaan Republik Indonesia - Muhammad Basri; Afrah Nadhilah Hasibuan; Khoiriyah Anggina Br Lubis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This article begins with the problems faced by Muslims. The struggle of Muslims to fight for Islam is indeed huge, but it is difficult for Muslims to make it happen, because the three great works of Islam are experiencing setbacks in various fields such as politics, military, economics, science and culture. I don't Can. The aim of this research is to create a reflection of Western colonialism in Islamic countries and consider its positive aspects. This research uses qualitative methods. The approach used is a historical approach. Based on this research, it was determined that the decline of the Islamic world was caused by Islamic kingdoms no longer having militant rulers and strong armies, giving rise to rebellions that were difficult to control. During. The progress experienced by the West was due to advances in science and civilization which were previously ignored in the development of the three great Islamic empires, especially the Ottoman Empire. The value reflected in this study is that Muslims are able to master all fields including military, science, culture, economics, politics, and other strategic fields, then they will win again.